Triple-functional bone adhesive with enhanced internal fixation, bacteriostasis and osteoinductive properties for open fracture repair - Yusheng Yang; Shenghui Su; Shencai Liu; Weilu Liu; Qinfeng Yang; Liangjie Tian; Zilin Tan; Lei Fan; Bin Yu; Jian Wang; Yanjun Hu (Bioactive Materials, 2023)
At present, effective fixation and anti-infection implant materials represent the mainstay for the treatment of open fractures. However, external fixation can cause nail tract infections and is ineffective for fixing small fracture fragments. Moreover, closed reduction and internal fixation during the early stage of injury can lead to potential bone infection, conducive to bone nonunion and delayed healing. Herein, we designed a bone adhesive with anti-infection, osteogenic and bone adhesion fixation properties to promote reduction and fixation of open fractures and subsequent soft tissue repair. It was prepared by the reaction of gelatin (Gel) and oxidized starch (OS) with vancomycin (VAN)-loaded mesoporous bioactive glass nanoparticles (MBGNs) covalently cross-linked with Schiff bases. Characterization and adhesion experiments were conducted to validate the successful preparation of the Gel-OS/VAN@MBGNs (GOVM-gel) adhesive. Meanwhile, in vitro cell experiments demonstrated its good antibacterial effects with the ability to stimulate bone marrow mesenchymal stem cell (BMSCs) proliferation, upregulate the expression of alkaline phosphatase (ALP) and osteogenic proteins (RunX2 and OPN) and enhance the deposition of calcium nodules. Additionally, we established a rat skull fracture model and a subcutaneous infection model. The histological analysis showed that bone adhesive enhanced osteogenesis, and in vivo experiments demonstrated that the number of inflammatory cells and bacteria was significantly reduced. Overall, the adhesive could promote early reduction of fractures and antibacterial and osteogenic effects, providing the foothold for treatment of this patient population.